Dosing time dependent in vitro pharmacodynamics of Everolimus despite a defective circadian clock. Issue 1 (2nd January 2018) - Zhang, Yuan; Giacchetti, Sylvie; Parouchev, Alexandre; Hadadi, Eva; Li, Xiaomei; Dallmann, Robert; Xandri-Monje, Helena; Portier, Lucie; Adam, René; Lévi, Françis; Dulong, Sandrine; Chang, Yunhua
ABSTRACT: Everolimus (EV), a rapamycin analogue mTOR inhibitor, is used in the clinic to treat Estrogen positive (ER + ) breast cancer in order to avoid the resistance to hormonotherapy. Here, we investigated whether EV efficacy varied according to administration timing by using the ER + breast cancer cell line MCF-7 as model system. Our results showed that instead of apoptosis, EV induced a G0/G1 phase blockage of MCF-7 cells. Following serum shock, MCF-7 cells displayed a statistically significant 24h rhythm of mammalian target of Rapamycin (mTOR) activity, but perturbed circadian clock genes oscillations. Interestingly, the different delivery schedule of EV presented different efficacy in G0/G1 phase blockage in serum shocked MCF-7 cells. Moreover, serum shock induced also a circadian-like oscillation in expression or activity of several important G1 phase progression proteins, such as Cyclin D1 and phosphorylated Retinoblastoma protein (RB). Inhibition mTOR activity by EV reduced Cyclin D1 and Cyclin D3 protein level as well as RB phosphorylation level. Taken together, the results indicated that serum shock synchronization induced a circadian oscillation in mTOR activity in MCF-7 cells, which rhythmically regulated the synthesis or phosphorylation of key G1 progression proteins, such as Cyclin D1 and phosphorylated RB, ultimately resulting in different G0/G1 blockage efficiency according to different EV administration timing.